CFD simulations of gas-solid flows in a CFB riser: Effect of inlet boundary conditions - Shah, M.; Utikar, Ranjeet; Evans, G.; Tade, Moses; Pareek, Vishnu (2011)
In this study, the effect of types of inlet and wall boundary conditions on the gas-solid flow fields in circulating fluidized bed risers was investigated using Eulerian-Eulerian simulations in both 2D and 3D domains. The 2D simulations were conducted using 3 different inlet configurations: (a) solids entering in radial direction from a two-sided inlet and gas entering axially from the bottom inlet, (b) solid entering axially from two-sided bottom inlet near the wall and gas entering axially from a bottom inlet at the centre, and (c) gas phase entering axially from two-sided bottom inlet near the wall and solids entering axially from a bottom inlet at the centre. From the 2D simulations, it was found that both the time-averaged axial velocity and solids volume fraction radial profiles were functions of the inlet kinetic energy profiles and gas-solid mixing patterns of each of the inlet configurations. Whilst 2D simulations using boundary conditions (a) and (c) showed significant deviations from experimental profiles, the boundary condition (b) as well as full-scale 3D simulations gave reasonable agreements with experimental observations.